The multifaceted roles of mucins family in lung cancer: from prognostic biomarkers to promising targets - Yuan, Qinghong; Cai, Sirui; Chang, Yuanhang; Zhang, Junqi; Wang, Meng; Yang, Kun; Jiang, Dongbo (Frontiers in Immunology, 2025)
Lung cancer remains one of the leading causes of cancer-related deaths worldwide, highlighting the urgent need for enhanced diagnostic and therapeutic strategies. Mucins, a family of glycoproteins crucial for maintaining epithelial integrity and regulating immune responses, have emerged as promising biomarkers and therapeutic targets in the context of lung cancer. The expression patterns and functional roles of mucin family members significantly influence lung cancer progression, thereby shaping diagnostic and therapeutic approaches for this disease. A more detailed classification of mucin family members could facilitate diagnosis and patient assessments, as well as help identify potential therapeutic targets. This review thoroughly examines the latest advancements in understanding the role of mucins in lung cancer progression, prognosis, and treatment, while also highlighting knowledge gaps and opportunities for future research, thus providing new perspectives for the management of this disease.